Problems With the Implementation of Qanun Aceh Number 6 of 2014 Concerning Jinayat Law - Qotadah, Hudzaifah Achmad; Wakhid, Ali Abdul; Susanto, Is (Universitas Islam Negeri Raden Intan Lampung, 2022)
Aceh as part of the Unitary State of the Republic of Indonesia has special privileges and autonomy, one of which is the authority to implement Islamic sharia, and Qanun Aceh Number 6 of 2014 concerning jinayat Law is part of Islamic law which is implemented in Aceh through the struggle of the Acehnese people in the application of Islamic sharia. However, after it was ratified, the implementation of the qanun Aceh gave rise to various problems in various circles. Therefore, through qualitative research with literature studies and data analysis through a deductive frame of mind, this article attempts to analyze the problems that arise after the implementation of the qanun Aceh. The results of this study indicate that the implementation of the qanun Aceh raises various problems. The emergence of pros and cons among the community, academia and the government, is assumed to be a barrier to human togetherness and understanding. The content of the qanun which is considered not comprehensive and discriminatory in nature is contrary to the Constitution and a number of laws.